Experimental and Theoretical Comparable Study of Pure and Zinc Porphyrin Surface Modified ZnO Nanorod Arrays for Hybrid Solar Cell Applications - Samir M. AbdulAlmohsin ,; Ali Natheer Tuaimah,; Sadaq Kh.Ajeel , (University of Thi-Qar Journal of Science, 2020)
Experimental and theoretical study Porphyrin-grafted ZnO nanowire arrays were investigated for organic/inorganic hybrid solar cell applications. Two types of porphyrin – Tetra (4-carboxyphenyle) TCPP and meso-Tetraphenylporphine (Zinc-TPP)were used to modify the nanowire surfaces. The vertically aligned nanowires with porphyrin modifications were embedded in graphene-enriched poly (3-hexylthiophene) [G-P3HT] for p-n junction nanowire solar cells. Surface grafting of ZnO nanowires was found to improve the solar cell efficiency. There are different effect for the two types of porphyrin as results of Zn existing. Annealing effects on the solar cell performance were investigated by heating the devices up to 225 °C in air. It was found that the cell performance was significantly degraded after annealing. The degradation was attributed to the polymer structural change at high temperature as evidenced by electrochemical impedance spectroscopy measurements.